The relationship between perceived parental acceptance-rejection and childhood traumas, self destructive behavior and suicidal ideation in cannabis users - İnci, Sevim Berrin; İpçi, Melis; Ender Altıntoprak, Ayşe; Akyol Ardıç, Ülkü; Ercan, Eyüp Sabri (Journal of Dependence, 2016)
Objective: The purpose of the study was to explore the relationship between perceived parental acceptance-rejection in childhood and childhood traumas, self destructive behavior and suicidal ideation.Method: The sample consisted of 75 cannabis users men who were enrolled in probationers from substance dependence unit in department of Psychiatry of the Ege University during the first consultation and control group that includes 75 men aged between 18-45 years of age. Data were collected via the Demographic Information Form, Parental AcceptanceRejection Questionnaire and Suicidal Behavior scale. MANOVA, Regression, t-test and Pearson Correlation Coefficient were performed.Results: The results showed that cannabis users perceived more reject from their parents. The findings revealed that there is a relationship between perceived parental acceptancerejection and physical, verbal and emotional abuse in childhood. Cannabis users were more exposed to trauma in childhood than control group. In addition, self-destructive behavior was associated with perceived acceptance from father, also suicial ideation was significantly associated with perceived acceptance from mother.Conclusion: This study revealed that parental acceptance-rejection in cannabis users should be considered as a significant variable for self-destructive behavior and suicidal ideation.
Keywords: Parental acceptance-rejection; self-destructive behavior; suicide; child abuse